Columellar-Frenulum Angle - A Significant Clinical Parameter in Assessing the Degree of Severity in Unilateral Cleft Lip. (May 2016) - Vathulya, Madhubari; Jain, Pradeep
Objectives: The study was carried out to learn if the columellar-frenulum angle could be used as one of the most important anthropometric measurements to predict the clinical severity in unilateral cleft lip patients. Settings and Design: This is a prospective case series conducted at Banaras Hindu University, Varanasi, India. Methods and Material: The study was based on the Thomson and Reinders criteria (1995), and various anthropometric measurements, including the columellar-frenulum angle, were measured. A total of 30 patients (21 boys and 9 girls) were included in the study. The ages of the children varied from 4 months to 15 years. The left side was affected in 18 patients, and 2 gave a significant positive family history. All the patients were subjected uniformly to Tennison's cleft lip repair. Patients with strictly unilateral complete cleft lip and palate were included in the study. Microform clefts, incomplete cleft lips, and bilateral clefts were excluded from the study. Statistical Analysis: The data was analyzed using Pearson's correlation coefficient. Results: The CF angle correlated negatively with the soft tissue defect of the cleft, cutaneous lip length, and vermilion lip length discrepancies from normal and soft tissue width just behind the alveolus. Conclusions: CF angle promises to offer a method by which prognosis of clefts can be predicted in terms of its severity in patients with unilateral cleft lip.